1993
DOI: 10.3758/bf03197190
|View full text |Cite
|
Sign up to set email alerts
|

Induction of combination rules in two-dimensional function learning

Abstract: Previous studies have typically found that when people learn to combine two dimensions of a stimulus to select a response, they learn additive combination rules more easily than nonadditive (e.g., multiplicative) ones. The present experiments demonstrate that in some situations people can learn multiplicative rules more easily than other (e.g., additive) rules. Subjects learned to produce specified response durations when presented with stimulus lines varying in length and angle of orientation. When stimuli an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Several studies have already been performed indicating the feasibility oftraining subjects to judge sensation magnitude on a standard scale. King and Lockhead (198 I), Koh and Meyer (1991), Koh (1993), West and Ward (1994), and Marks, Galanter, and Baird (1995) have all provided evidence that, given feedback, subjects can learn to respond to sensory stimuli according to power functions with a given exponent, quickly and with a high degree of accuracy. In addition, West and Ward (1994) and Marks et al (1995) addressed the issue of using learned scales to investigate basic psychophysical phenomena.…”
Section: Law)mentioning
confidence: 99%
“…Several studies have already been performed indicating the feasibility oftraining subjects to judge sensation magnitude on a standard scale. King and Lockhead (198 I), Koh and Meyer (1991), Koh (1993), West and Ward (1994), and Marks, Galanter, and Baird (1995) have all provided evidence that, given feedback, subjects can learn to respond to sensory stimuli according to power functions with a given exponent, quickly and with a high degree of accuracy. In addition, West and Ward (1994) and Marks et al (1995) addressed the issue of using learned scales to investigate basic psychophysical phenomena.…”
Section: Law)mentioning
confidence: 99%
“…If novel stimuli are presented outside the range of training values, participants are capable of extrapolation, albeit at a lower level of accuracy than interpolation (DeLosh, . Although it is possible for people to learn functions that map multiple stimulus dimensions onto a single response dimension (e.g., Koh, 1993;Roe, Barkan, & Busemeyer, 2001), most research to date has been conducted with one-dimensional functions in which a single stimulus property determines each response. This article is primarily concerned with one-dimensional function learning.…”
Section: Learning Function Conceptsmentioning
confidence: 99%
“…Additive combinations of linear functions are more efficiently learned than nonadditive combinations (Brehmer 1969;Klayman 1988). However, previous work on rule learning has shown that students sometimes learn multiplicative rules more effectively than additive rules when the criterion is not numerical (Koh 1993). This explains the considerable improvement of the performances in the study by , even among the youngest participants.…”
Section: Resultsmentioning
confidence: 58%